The effects of using collaborative writing vs. peer review treatments on subsequent individual writings - Bueno Alastuey, Mª Camino; Rodero Albaiceta, Seila (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
revious research has investigated separately the effects of collaborative writing and peer review. However, there has not been any research comparing both approaches. This study is aimed to analyse the effects of those two treatments on a subsequent individually written production in terms of complexity ac-curacy, and fluency (CAF measures), as well as quality. The participants were 29 students of lower-intermediate English proficiency level, 16 in the collaborative writing group and 13 in the peer review group. Two compositions were ana-lysed as pre-test and post-test using CAF meas-ures and an analytic rubric. The results suggest that students in the collaborative writing group produced longer writings and more complex language, while those in the peer review group improved their final individual writing in terms of lexical variety and accuracy.
Keywords: collaborative writing; peer review; complexity; accuracy and fluency (CAF measures); lexical variety; EFL